A Survey of English Writing Competencies of Secondary School Students - Fazal ur Rahman, Jamila Hashmi (PJE, 2023)
English also has four basic skills of listening, speaking, reading & writing. Writing is the productive skill in written mode. Among four basic skills, writing is the hardest of the skills even for native speakers of a language as being more complicated than that of other language skill. The study aimed to assess the English writing competencies of secondary school students. It was descriptive study conducted in secondary schools of district Attock. Sample of the study consisted of 360 students (180 male and 180 female). Tool of study consisted of an achievement test for students consisting five areas of English writing competencies (vocabulary, sentence making, hand writing, comprehension, tenses) and a questionnaire for teachers. The data was analyzed using t-test for the purpose of measuring difference between the students’ performance. A test of correlation was used to find relationship between students’ competencies in sub skills of English writing competencies and their teachers’ usage of different strategies and techniques in class in teaching of these skills. The findings of the study showed that the use of multiple teaching techniques has a positive impact on development of English writing skills of students